Atomistic simulations to study crack tip behaviour in multi-elemental alloys. (15th February 2021) - Kumar Singh, Sandeep; Parashar, Avinash
Highlights: Atomistic simulations to study crack tip behavior in multi-elemental alloys. Orientation of crack plane switches the deformation governing mechanism. Perfect plastic conditions prevail in medium and high entropy alloys. Dislocations and stacking faults govern deformation in high entropy alloys. Abstract: The aim of the article is to study the crack tip behaviour in mutli-elemental alloys. Molecular dynamics based simulations were performed in conjunction with 2NN MEAM potential to study the fracture behaviour in ternary, quaternary, and quinary alloy configurations. Simulations were performed after aligning the crack plane with three different principle planes of FCC crystal. Deformation in each of the orientations was primarily governed by dislocations, twinning, and stacking faults emanating front the crack tips or from the surface of the crack plane. Medium and high entropy alloys have shown higher resistance to fracture, and were capable of retaining strength up to a larger extent as compared to low entropy alloy and pure Ni crystal. The higher dislocation density and uniform distribution of dislocation in medium and high entropy alloys leads to plasticity in the crystal after the onset of yielding. Blunting of the crack tip in medium and high entropy alloys was predicted in orientation 1 and 2, whereas crack propagates in orientation 3. This study will help in elucidating the capabilities of medium and high entropy alloys in resisting the opening mode of crack propagation, which can be further utilized to enhance the diversified structural applications of these emerging multi-elemental alloys.